High quality permanent draft genome sequence of Phaseolibacter flectens ATCC 12775T, a plant pathogen of French bean pods. Issue 1 (December 2016) - Aizenberg-Gershtein, Yana; Izhaki, Ido; Lapidus, Alla; Copeland, Alex; Reddy, TBK; Huntemann, Marcel; Pillay, Manoj; Markowitz, Victor; Göker, Markus; Woyke, Tanja; Klenk, Hans-Peter; Kyrpides, Nikos; et al.
Abstract Phaseolibacter flectens strain ATCC 12775T (Halpern et al., Int J Syst Evol Microbiol 63:268–273, 2013) is a Gram-negative, rod shaped, motile, aerobic, chemoorganotroph bacterium.Ph. flectens is as a plant-pathogenic bacterium on pods of French bean and was first identified by Johnson (1956) asPseudomonas flectens. After its phylogenetic position was reexamined, Pseudomonas flectens was transferred to the familyEnterobacteriaceae asPhaseolibacter flectens gen. nov., comb. nov. Here we describe the features of this organism, together with the draft genome sequence and annotation. The DNA GC content is 44.34 mol%. The chromosome length is 2, 748, 442 bp. It encodes 2, 437 proteins and 89 RNA genes.Ph. flectens genome is part of the Genomic Encyclopedia of Type Strains, Phase I: the one thousand microbial genomes study.